Environmental drivers of nitrous oxide emission factor for a coastal reservoir and its catchment areas in southeastern China. (1st February 2022) - Yang, Ping; Luo, Liangjuan; Tang, Kam W.; Lai, Derrick Y.F.; Tong, Chuan; Hong, Yan; Zhang, Linhai
Abstract: While Asia is projected to be one of the major nitrous oxide (N2 O) sources in the coming decades, a more accurate assessment of N2 O budget has been hampered by low data resolution and poorly constrained emission factor (EF). Since urbanized coastal reservoirs receive high nitrogen loads from diverse sources across a heterogeneous landscape, the use of a single fixed EF may lead to large errors in N2 O assessment. In this study, we conducted high spatial resolution sampling of dissolved N2 O, nitrate-nitrogen (NO3 − –N) and other physico-chemical properties of surface water in Wenwusha Reservoir and other types of water bodies (river, drainage channels, and aquaculture ponds) in its catchment areas in southeastern China between November 2018 and June 2019. The empirically derived EF (calculated as N2 O–N:NO3 − -N) for the reservoir showed considerable spatial variations, with a 10-fold difference ranging from 0.8 × 10 −3 to 8.8 × 10 −3 . The average EF varied significantly among the four types of water bodies in the following descending order: aquaculture ponds > river > drainage channels > reservoir. Across all the water bodies, the mean EF in summer was 1.8–3.5 and 1.7–2.8 fold higher than that in autumn and spring, respectively, owing to the elevated water temperature. Overall, our derived EF deviated considerably from the IPCC default value, which implied that the use of default EF could result in over- or under-estimation of N2 O emissions by up to 42%. We developed a multiple regression model that could explain 82% of the variance in EF based on water temperature and the ratio between dissolved organic carbon and nitrate-nitrogen ( p < 0.001), which could be used to improve the estimate of EF for assessing N2 O emission from coastal reservoirs and other similar environments. Graphical abstract: Image 1 Highlights: Coastal reservoirs are a strong source of nitrous oxide (N2 O). N2 O emission factor (EF) varied widely across different water types. Water temperature ( T w ) affected seasonal variations in EF. Assessment of N2 O emissions using a fixed EF would introduce large errors. EF was best predicted by T w, dissolved organic carbon and nitrate concentration.